2015
DOI: 10.1515/polyeng-2015-0267
|View full text |Cite
|
Sign up to set email alerts
|

Numerical investigation of the temperature influence on the melt predistribution in a spiral mandrel die with different polyolefins

Abstract: Abstract The main goal in the design of spiral mandrel dies for blown film extrusion is to achieve a homogeneous velocity distribution of the plastics melt at the die outlet. However, thermal inhomogeneities in the die can lead to an uneven flow distribution despite a rheologically optimized design of the die. The thermal inhomogeneities are especially dominant in the predistributor of spiral mandrel dies. Against this background, the temperature influence on the melt distribut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…Hopmann and Yesildag 2,3 analyzed how thermal inhomogeneity affects the flow distribution in the die pre-distributors. They considered dissipative shear heating and the external die heating as two possible reasons for the temperature gradient in the die pre-distributors, and reported that both parameters have a significant effect in producing an uneven flow distribution in the 2 n -pre-distributors; however, the external die heating had negligible effect in the star-pre-distributors.…”
Section: Introductionmentioning
confidence: 99%
“…Hopmann and Yesildag 2,3 analyzed how thermal inhomogeneity affects the flow distribution in the die pre-distributors. They considered dissipative shear heating and the external die heating as two possible reasons for the temperature gradient in the die pre-distributors, and reported that both parameters have a significant effect in producing an uneven flow distribution in the 2 n -pre-distributors; however, the external die heating had negligible effect in the star-pre-distributors.…”
Section: Introductionmentioning
confidence: 99%